FPGAs and Parallel Architectures for Aerospace Applications Soft Errors and Fault-Tolerant Design - Kastensmidt, Fernanda; Rech, Paolo; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book introduces the concepts of soft errors in FPGAs, as well as the motivation for using commercial, off-the-shelf (COTS) FPGAs in mission-critical and remote applications, such as aerospace.  The authors describe the effects of radiation in FPGAs, present a large set of soft-error mitigation techniques that can be applied in these circuits, as well as methods for qualifying these circuits under radiation.  Coverage includes radiation effects in FPGAs, fault-tolerant techniques for FPGAs, use of COTS FPGAs in aerospace applications, experimental data of FPGAs under radiation, FPGA embedded processors under radiation, and fault injection in FPGAs. Since dedicated parallel processing architectures such as GPUs have become more desirable in aerospace applications due to high computational power, GPU analysis under radiation is also discussed. ·         Discusses features and drawbacks of reconfigurability methods for FPGAs, focused on aerospace applications; ·         Explains how radiation from space causes soft errors in FPGAs and how to mitigate them; ·         Enables readers to qualify the target application on FPGA under radiation and by fault injection.
Programmable Logic and Parallel Architectures for Space Applications -- Applications -- Brazilian Nano-satellite with Reconfigurable SOC GNSS Receiver Tracking capability -- Overview and Investigation of SEU Detection and Recovery Approaches for FPGA-based Heterogeneous Systems -- SRAM-based FPGAs -- A Fault injection technique oriented to SRAM-FPGAs -- Fault Injection System for Measuring Soft Processor Design Sensitivity on Virtex-5 FPGAs -- Hybrid Configuration Scrubbing for Xilinx Series-7 FPGAs -- N-MR Techniques for SRAM-based FPGAs and Power Analysis -- Fault-Tolerant Manager Core for Dynamic Partial Reconfiguration in FPGAs -- Multiple Fault Injection FPGA Platform based on Ground-level Radiation Experiments.
Keywords: Electronic circuits; Microprocessors; Computer architecture; Electronic Circuits and Systems; Processor Architectures